2009
DOI: 10.2319/061008-300.1
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Brackets Rebonded with a Fluoride-Releasing and -Recharging Adhesive System

Abstract: Objective: To ascertain the effects of repeated bonding on the shear bond strength of orthodontic brackets bonded with a fluoride-releasing and -recharging adhesive system with a self-etching primer in comparison with two other types of adhesive system. Materials and Methods: A total of 48 premolars were collected and divided equally into three groups of 16. Each group was assigned one of three adhesive systems: Transbond XT, Transbond Plus, or a fluoride-releasing and -recharging adhesive system, Beauty Ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The null hypothesis tested that there were no significant differences in SBS between the orthodontic bracket bonding system using resin coating material and the previous orthodontic bracket bonding systems was partially rejected. Some investigators have reported that the SBS of the resin composite cement (Transbond XT, 3M Unitek) system was comparable with that of the RMGIC system 6) , while others have reported that it was significantly higher than that of the resin composite cement (BOB) system with the self-etching primer 14) . Based on these previous findings, our result showing that the RMGIC system (group 1, 11.7 MPa) exhibited a significantly higher mean SBS than the BOB system combined with the self-etching primer (group 2, 9.6 MPa) might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis tested that there were no significant differences in SBS between the orthodontic bracket bonding system using resin coating material and the previous orthodontic bracket bonding systems was partially rejected. Some investigators have reported that the SBS of the resin composite cement (Transbond XT, 3M Unitek) system was comparable with that of the RMGIC system 6) , while others have reported that it was significantly higher than that of the resin composite cement (BOB) system with the self-etching primer 14) . Based on these previous findings, our result showing that the RMGIC system (group 1, 11.7 MPa) exhibited a significantly higher mean SBS than the BOB system combined with the self-etching primer (group 2, 9.6 MPa) might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest damage to the enamel during debonding, this could be due to; the debonding method, bracket type, mesh type, surface area of the mesh, etching method, or the adhesive system (Bosh, Kaufman, Balabanovsky, & Vardimon, 2015; Endo et al, 2009; Pickett et al, 2001; Samruajbenjakul & Kukiattrakoon, 2009). In the present study, enamel loss occurred in 10% of the total samples, which is evident through the presence of enamel prisms in the images obtained through SEM.…”
Section: Discussionmentioning
confidence: 99%
“…The present study obtained values of G1 = 10.09 ± 2.73 MPa, G2 = 9.27 ± 3.99 MPa, G3 = 7.83 ± 4.46 MPa, and G4 = 6.40 ± 2.85 MPa, using different debonding methods (shear behind the upper fins) (Bosh et al, 2015). The adequate SBS for safety orthodontic debonding should be from 2.80 and 10 MPa so there is not a damage or enamel loss (Endo et al, 2009; Pickett et al, 2001; Samruajbenjakul & Kukiattrakoon, 2009). Nevertheless, we observed damages and enamel loss; this could be due to inclusion criteria, debonding method, debonding time, and bracket area.…”
Section: Discussionmentioning
confidence: 99%
“…Bond strengths between 6 and 8 MPa are clinically sufficient for successfully bonding orthodontic brackets to enamel [24][25][26][27][28] . Our findings showed that the shear bond strengths of all the 4 groups were higher than the clinically required range of 6 to 8 MPa.…”
Section: Discussionmentioning
confidence: 99%